The Effects of Adverse Events and Associated Costs on Value-Based Care for Metastatic Pancreatic Ductal Adenocarcinoma - Prachi Bhatt; Jared Hirsch; Paul Cockrum; George Kim; Gabriela Dieguez (Journal of Health Economics and Outcomes Research)
**Background:** Rising oncology healthcare costs have led to value-based care reimbursement models that coordinate care and improve quality while reducing overall spending. These models are increasingly important for traditional Medicare and other payers. **Objectives:** To compare the incidence of adverse events (AEs), AE-associated excess costs, and total cost of care (TCOC) of 3 cohorts receiving first-line treatment for metastatic pancreatic ductal adenocarcinoma (mPDAC). **Methods:** We conducted a retrospective analysis of administrative claims data from 2018 to 2022 using the Medicare 100% Research Identifiable Files. We examined 3 cohorts receiving mPDAC treatment: FOLFIRINOX (FFX) (oxaliplatin, irinotecan, leucovorin, 5-FU bolus and infusion); modified FFX, (5-FU infusion only); and gemcitabine/nab-paclitaxel (gem/abrax). We compared the incidence of clinically significant AEs, TCOC, components of TCOC, and costs related to AEs/treatment toxicity. **Results:** Patient AE rates ranged from 6.2% to 51.7%. AEs occurred more frequently in patients receiving FFX with all 4 components. Patients receiving brand name gem/abrax had lower rates of febrile neutropenia (6.2%) and neutropenia (22.2%) than those receiving FFX with no 5-FU bolus (febrile neutropenia, 9.9%; neutropenia, 36.9%) and FFX with all 4 components (febrile neutropenia, 6.9%; neutropenia, 30.4%). Rates of most nonhematologic AEs were higher in patients receiving FFX with all 4 components, with diarrhea occurring in 28.3%, abdominal pain in 31.5%, and nausea/vomiting in 41.5% of patients. TCOC was lower in the gem/abrax cohort: $6505 vs FFX with no 5-FU bolus ($6995) and FFX with all 4 components ($7142) per administration. The development of any studied hematologic AE was associated with a mean excess cost of $5993 per administration, while the development of any studied nonhematological AE was associated with a mean per-administration excess cost of $3665. **Discussion:** Treatment decisions intended to minimize chemotherapy costs may lead to suboptimal decisions if the goal is to reduce TCOC. Our research suggests FFX is more costly than gem/abrax (TCOC per administration). Patients receiving gem/abrax were older and had higher baseline Charlson Comorbidity Index scores; however, other factors may be important in driving cost differences. **Conclusions:** Irrespective of drug cost, chemotherapy leading to a significant increase in AEs is associated with higher TCOC.